Legume Crops Characterization and Breeding for Improved Food Security - Ahmed El-Esawi, Mohamed (IntechOpen, 2019)
Legumes are flowering plants found in most of the archeological records of plants. Legumes are efficiently used as food crops for humans and animals, pulps for paper and timber manufacturing, sources for fuel and oil production, ornamental plants, and cover crops such as cereals and other staple foods. Additionally, they can be utilized for other purposes, including the production of massive amounts of organic nitrogen. This book reviews the fundamental advances related to the characterization and breeding of legume crops for improved food security. Moreover, it sheds new light on the current research trends and future research directions related to legume crop studies. This book will provoke interest for various readers, researchers, and scientists, who may find this information useful for the advancement of legume productivity.